Synthesis, characterization and use of Poly (N-isopropylacrylamide-co-N-vinylcaprolactam) crosslinked thermoresponsive microspheres for control release of Ciproflaxin hydrochloride drug - B. Mallikarjuna, K. Madhu Sudhana Rao, C.V. Prasad, K.Chowdoji Rao, K.S.V. Krishana Rao, M.C.S. Subha (Journal of Applied Pharmaceutical Science)
Poly (N-isopropylacrylamide-co-N-vinyl caprolactam) copolymer was synthesized as an interesting thermoresponsive material possessing a phase transition temperature around 320C in phosphate buffer, pH 7.4 (PB). Thermoresponsive Poly(N-isopropylacrylamide-co-Nvinylcaprolactam) designated as PNIPA-NVC microspheres crosslinked with N,N’–methylene bisacrylamide (NNMBA) have been prepared by dispersion polymerization using varying amounts of NIPA, NVC and NNMBA., ciproflaxin hydrochloride (CFH) an anti- bacterial drug, was loaded into the microspheres during in situ polymerization and in vitro release of CFH has been studied. The microspheres were characterized by Fourier Transform Infrared Spectroscopy (FTIR) Differential Scanning Calorimetry (DSC), X-Ray Diffractometry (X- RD) and Scanning Electron Microscopy (SEM). The in-vitro release of CFH drug from the microspheres was studied in pH 7.4 medium, at the temperatures 250C & 370C. The microspheres consisting of NIPA and NVC provide thermo responsive nature to the microspheres. The system developed in this study showed a thermoresponsive for the controlled release of CFH. FTIR spectroscopy explained the formation of copolymer. The DSC and XRD techniques indicated the uniform distribution of drug in the microspheres. SEM studies indicated surface morphology of the microspheres. Prolonged and controlled release of CFH was achieved in a controlled manner upto 12 h.
Keywords: Microspheres, NIPA, NVC, Ciproflaxin hydrochloride (CFH), Drug delivery.